Exploration of children’s value patterns in relation to environmental education programmes - Kelly, Tim; Bouman, Thijs; Kemp, Simon; Wijngaarden, Franka; Grace, Randolph C. (Frontiers in Psychology, 2023)
During childhood we begin to develop values, including valuing the natural environment (biospheric values). Although biospheric values are believed to provide the foundation for pro-environmental behavior throughout the course of one’s life, little research has investigated these values in children. The present study aimed to investigate the relationships between children’s endorsement of biospheric values, their pro-environmental behaviors, and their perception of their friends’ and peers’ endorsement of biospheric values. Moreover, we investigated whether these values and behaviors, as well as the hypothesized relationships, were affected by educational programmes that were already implemented at schools. The results showed that children generally strongly endorse biospheric values, and that biospheric values were positively related to some personal and group pro-environmental behaviors. The study also found that, as in previous research with adults, the participants believed that their friends and peers endorsed biospheric values significantly less than they themselves did. Environmental educational programs were partially effective in reducing the participants’ underestimation of their friends’ biospheric values and increased the likelihood of some group pro-environmental behaviors. Our findings highlight the need for further research to investigate the effects of group pro-environmental behaviors and the perception of group values.